Analysis of anthropometric profiles and long-term career progression in 24 years of German junior rowing - Winkert, K.; Treff, G.; Lormes, W.; Machus, K.; Steinacker, J. M. (Medicine & Science in Sports & Exercise, 2017)
Talent identification in rowing typically includes standing height (SH) and body mass (BM), because successful rowers are on average taller and heavier than their opponents. Moreover, successful elite senior rowers are significantly taller and heavier than Juniors, but it remains unclear if those athletes who became elite rowers later, were already taller and heavier as adolescents.